Modulation of beta 1-integrins on hemopoietic progenitor cells after allergen challenge in asthmatic subjects - Catalli, Adriana E; Thomson, Jennifer V; Babirad, Irene M; Duong, MyLinh; Doyle, Tracey M; Howie, Karen J; Newbold, Paul; Craggs, Richard I; Foster, Martyn; Gauvreau, Gail M; O'Byrne, Paul M; Sehmi, Roma (Journal of allergy and clinical immunology, 2008)
Mobilization of hemopoietic progenitor cells from the bone marrow (BM) is a feature of inflammatory asthmatic responses. Understanding the mechanisms regulating progenitor cell mobilization and trafficking to the peripheral circulation might be important for the development of effective asthma therapies. Objective - We investigated the role of adhesion molecules in the mobilization of hemopoietic progenitor cells from the BM during an allergen-induced asthmatic response. Methods - BM and peripheral blood samples were obtained from dual-responders with mild asthma before and at several time points after allergen challenge. Fluctuations in expression and adhesive properties of beta 1- and beta 2-integrins on CD34 super(+)CD45 super(+) progenitor cells were assessed by using flow cytometry and adhesion to protein-coated wells, respectively. Results - On BM-derived CD34 super(+)CD45 super(+) cells, expression of very late antigen (VLA) 4, but not VLA-5 or Mac-1, decreased significantly 24 hours after allergen challenge and had begun to recover by 48 hours after challenge. In peripheral blood allergen challenge induced a significant decrease in VLA-4 levels after 6 hours, which had not recovered by 96 hours after challenge. Similarly, VLA-5 expression decreased, most prominently at 72 to 96 hours after allergen challenge. In contrast, Mac-1 levels did not change. Chemokine- stimulated adhesion of BM-derived CD34 super(+)CD45 super(+) cells to fibronectin was significantly attenuated 24 hours after challenge. Furthermore, adhesion to fibronectin and vascular cell adhesion molecule 1 was greatly reduced by anti-VLA-4 or anti-VLA-5 antibodies. Conclusions - Preferential downregulation of beta 1- integrin expression on progenitor cells can reduce the tethering forces to BM components, thus facilitating their egress to the peripheral circulation during an allergic inflammatory response.